Biocommunication in soil microorganisms - Witzany, Günther (Springer eBooks., 2011)
Communication is defined as an interaction between at least two living agents which share a repertoire of signs. These are combined according to syntactic, semantic and context-dependent, pragmatic rules in order to coordinate behavior. This volume deals with the important roles of soil bacteria in parasitic and symbiotic interactions with viruses, plants, animals and fungi. Starting with a general overview of the key levels of communication between bacteria, further reviews examine the various aspects of intracellular as well as intercellular biocommunication between soil microorganisms. This includes the various levels of biocommunication between phages and bacteria, between soil algae and bacteria, and between bacteria, fungi and plants in the rhizosphere, the role of plasmids and transposons, horizontal gene transfer, quorum sensing and quorum quenching, bacterial-host cohabitation, phage-mediated genetic exchange and soil viral ecology.